2015
DOI: 10.1007/s12640-015-9543-y
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise Alleviates Health Defects, Symptoms, and Biomarkers in Schizophrenia Spectrum Disorder

Abstract: Schizophrenia spectrum disorders are characterized by symptom profiles consisting of positive and negative symptoms, cognitive impairment, and a plethora of genetic, epigenetic, and phenotypic biomarkers. Assorted animal models of these disorders and clinical neurodevelopmental indicators have implicated neurodegeneration as an element in the underlying pathophysiology. Physical exercise or activity regimes--whether aerobic, resistance, or endurance--ameliorate regional brain and functional deficits not only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 165 publications
0
11
0
Order By: Relevance
“…Studies have demonstrated the efficacy of aerobic exercise in treating the cognitive and biochemical deficits found in SCH patients (Archer and Kostrzewa, 2015). In addition to enhanced expression of insulin-like growth factor (IGF)-1 and BDNF (Kim et al, 2014;Kuo et al, 2013), people suffering from SCH who led an active lifestyle had lower levels of serum CRP when compared to the sedentary control population (Stubbs et al, 2015).…”
Section: Anti-inflammatory Effects Of Physical Activity and Exercise mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated the efficacy of aerobic exercise in treating the cognitive and biochemical deficits found in SCH patients (Archer and Kostrzewa, 2015). In addition to enhanced expression of insulin-like growth factor (IGF)-1 and BDNF (Kim et al, 2014;Kuo et al, 2013), people suffering from SCH who led an active lifestyle had lower levels of serum CRP when compared to the sedentary control population (Stubbs et al, 2015).…”
Section: Anti-inflammatory Effects Of Physical Activity and Exercise mentioning
confidence: 99%
“…Experimental and epidemiological studies have demonstrated that living a healthy and physically active lifestyle reduces the risk (Barnes and Yaffe, 2011;Scarmeas et al, 2009;Zou et al, 2015) and severity of neurological diseases (Archer and Kostrzewa, 2015;Canning et al, 2015;Erickson et al, 2012;Eyre and Baune, 2012;Frazzitta et al, 2015;Frazzitta et al, 2014;Liu et al, 2013;Radak et al, 2007;Radak et al, 2013;Suijo et al, 2013;Uc et al, 2014;Yu et al, 2014). However, the cellular and molecular mechanisms responsible for these beneficial effects of PA have not been established.…”
Section: Summary and Hypothesesmentioning
confidence: 99%
“…resulting in subjective or objective binge eating episodes for example, often induced by the failure of restriction to dietary rules [2]. These notions support the essential over-evaluation of weight and shape and that this cognitive mind-set in its turn influences the attempts at eating restraint [3]. It has been observed also that low individual self-esteem exerts a general influence on over-evaluation of weight and shape [4].…”
Section: Editorialmentioning
confidence: 86%
“…Regular exercise aimed at patients with schizophrenia can help to reduce body mass index, improve psychiatric symptoms, and lead to feelings of accomplishment and therefore provide an impact on quality of life. (19)(20)(21) In this sense, managers and professionals who work with this population should support the need for planning and implementation of initiatives to promote and encourage this practice in the routine of health services, including seeking of intersectoral partnerships.…”
Section: Discussionmentioning
confidence: 99%